Gene Wiki Reviews—Raising the quality and accessibility of information about the human genome - Tsueng, Ginger; Good, Benjamin M.; Ping, Peipei; Golemis, Erica; Hanukoglu, Israel; van Wijnen, Andre J.; Su, Andrew I. (Gene, 2016)
Wikipedia and other openly available resources are increasingly becoming commonly used sources of information not just among the lay public but even in academic circles including undergraduate students and postgraduate trainees. To enhance the quality of the Wikipedia articles, in 2013, we initiated the Gene Wiki Reviews on genes and proteins as a series of invited reviews that stipulated editing the corresponding Wikipedia article(s) that would be also subject to peer-review. Thus, while the review article serves as an authoritative snapshot of the field, the “living article” can continue to evolve with the crowdsourcing model of Wikipedia. After publication of over 50 articles, we surveyed the authors to assess the impact of the project. The author survey results revealed that the Gene Wiki project is achieving its major objectives to increase the involvement of scientists in authoring Wikipedia articles and to enhance the quantity and quality of the information about genes and their protein products. Thus, the dual publication model introduced in the Gene Wiki Reviews series represents a valuable innovation in scientific publishing and biomedical knowledge management. We invite experts on specific genes to contact the editors to take part in this project to enhance the quality and accessibility of information about the human genome.